Proteolytically generated soluble Tweak Receptor Fn14 is a blood biomarker for γ‐secretase activity - Gökhan Güner; Marlene Aßfalg; Kai Zhao; Tobias Dreyer; Shibojyoti Lahiri; Yun Lo; Bianca Ionela Slivinschi; Axel Imhof; Georg Jocher; Laura Strohm; Christian Behrends; Dieter Langosch; et al. (EMBO Molecular Medicine)
Abstract Fn14 is a cell surface receptor with key functions in tissue homeostasis and injury but is also linked to chronic diseases. Despite its physiological and medical importance, the regulation of Fn14 signaling and turnover is only partly understood. Here, we demonstrate that Fn14 is cleaved within its transmembrane domain by the protease γ‐secretase, resulting in secretion of the soluble Fn14 ectodomain (sFn14). Inhibition of γ‐secretase in tumor cells reduced sFn14 secretion, increased full‐length Fn14 at the cell surface, and enhanced TWEAK ligand‐stimulated Fn14 signaling through the NFκB pathway, which led to enhanced release of the cytokine tumor necrosis factor. γ‐Secretase‐dependent sFn14 release was also detected ex vivo in primary tumor cells from glioblastoma patients, in mouse and human plasma and was strongly reduced in blood from human cancer patients dosed with a γ‐secretase inhibitor prior to chimeric antigen receptor (CAR)‐T‐cell treatment. Taken together, our study demonstrates a novel function for γ‐secretase in attenuating TWEAK/Fn14 signaling and suggests the use of sFn14 as an easily measurable pharmacodynamic biomarker to monitor γ‐secretase activity in vivo.